Validity and reliability of two core temperature measurement techniques during physical exercise in the heat: CORE SENSOR and EXERGEN TAT-5000 - Januário, William Martins (2023)
Methods: Eight men and eight women, regular cyclists (Age: 33.9±8 years; VO2max: 53.6±7.0 mL.kg−1.min−1) underwent two similar cycling trials in a controlled environment at 32°C, relative humidity 60%. The protocol consisted of an initial 10-minute rest, followed by an exercise protocol (60 minutes) in a hot environment, comprising 10 minutes at 20% of maximal aerobic power, 25 minutes at 55%, and 25 minutes at 75%, with an additional 25 minutes of post-exercise recovery. Core temperature was recorded simultaneously every minute using a gastrointestinal capsule (TCAPSULE) and the CORE Sensor (TCORE). Bland–Altman analysis was performed to calculate bias, upper (LCS) and lower (LCI) concordance limits, and the 95% confidence interval (CI95%). The maximum acceptable difference between the two devices was ±0.4°C. A mixed linear model was used to model the paired differences between the two measurement systems, considering the subjects, reliability and environmental conditions as random effects and the activities as a fixed effect. Results: The CORE Sensor recorded an ICC value of 0.98. A non-significant bias value of 0.01, LCS of 0.38°C, LCI of -0.35°C and 95% CI of ±0.36°C were found. The Exergen TAT-5000 recorded an ICC value of 0.90. A significant bias value of -0.59, LCS of 0.82°C, LCI of -2.05°C and 95% CI of ±1.44°C were found. Conclusion: Compared to TCAPSULE, the CORE Sensor was considered valid and reliable in estimating core temperature during cycling exercise in a hot environment. Compared to TCAPSULE, the Exergen TAT-5000 was considered reliable but invalid in estimating core temperature during cycling exercise in a hot environment.KEYWORDS Body Temperature; Cycling Exercise; Heat Wave; Thermometers; Heat Illnesses.